2013
DOI: 10.1007/s10029-013-1115-6
|View full text |Cite
|
Sign up to set email alerts
|

Closure versus non-closure of hernia defect during laparoscopic ventral hernia repair with mesh

Abstract: Although our study demonstrated a difference in recurrence rates of 19.18 % in the non-closure group versus 6.25 % in the closure group, the difference did not reach statistical significance. A larger series with longer follow-up may demonstrate clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 27 publications
2
55
1
Order By: Relevance
“…The technique they described comprised of using smooth sutures in closing the defects and fixing meshes with transcutaneous non-absorbable sutures without any staples or tacks. From a study describing laparoscopic repair with mesh of 128 patients, Zeichen et al [12] reported no statistical differences in recurrence rates between the non-closure and closure groups.…”
Section: Discussionmentioning
confidence: 99%
“…The technique they described comprised of using smooth sutures in closing the defects and fixing meshes with transcutaneous non-absorbable sutures without any staples or tacks. From a study describing laparoscopic repair with mesh of 128 patients, Zeichen et al [12] reported no statistical differences in recurrence rates between the non-closure and closure groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we reviewed the literature on IPOMPlus, including the details of the surgical procedures and outcomes using the PubMed database for papers published between 1993 and April 2015 using the terms laparoscopic AND (ventral or incisional) AND hernia AND (defect closure or augmentation repair) as keywords, and 16 relevant articles [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were reviewed. Out of these articles, four [30,31,33,34] compared sIPOM with IPOM-Plus, and only one report was a randomized controlled study (RCT) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of this event occurring in IPOM plus is reported as 0-11.43% [15] . Its occurrence IPOM plus as compared to standard IPOM surgery is controversial as different studies have reported IPOM plus to have better outcomes [27] , similar outcomes [31] or worse outcomes [32] as compared to IPOM surgery. Chronic pain, i.e., pain perceived at operative site beyond 6 months, was reported by 5 of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In both the cases, IPOM plus repair was done laparoscopically. Literature favors IPOM plus with a lower incidence of recurrences as compared to standard IPOM surgery [32,33] . Improvement in functional status of abdominal muscles has been reported after an IPOM Plus repair.…”
Section: Discussionmentioning
confidence: 99%